Analysis Of Bank-Spesific Factors To Determine The Profitability Of Islamic Banks In Indonesia : A Panel Regression Approach - Nur’aini, Dyah Tari (Buletin Studi Ekonomi, 2020)
Profitability is an important indicator of the bank’s performance. In 2014, profits of Islamic s bank in Indonesia decreased by 19.7 percent. This paper aims to analyze the impact of bank-specific factors to The Islamic banking system in Indonesia has shown better development Islamic bank’s profitability. This study observed 11 Islamic banks in the Indonesia banking system in the period between 2010 - 2014. The quarterly data are taken from the Indonesian Banking Directory, published by the Financial Service Aut h ority (OJK). Using panel data regression, the Fixed Effect Model with cross-sectional correlation (SUR) has selected as the best model . According to the obtained results, among internal factors of bank profitability, the most important one is the operating efficiency ratio . Furthermore, profitability is influenced negatively by liquidity risk, solvency risk, credit risk, and bank size.